Effect of Cryptococcal Capsular Compounds on Blood Coagulation in Animal Models - AR Salehie-Nodeh;N Ashkanizadeh;MR Nikooie-Mogaddam;A Mirshafieii (Iranian Journal of Public Health, 2005)
Glucoronoxylomannan (GXM) is the most important compound of polysaccharide capsule in Cryptococcus neoformans that causes infection in its recognition as a foreign agent by immune system. Because of its similarity with some naural compounds such as heparin and hyaloronic acid, this study was undertaken to determine the effect of polysaccharide compounds on blood coagulative process and renal performance in two groups of laboratory animals including Guinea pig and rat via interaperitoneal injection of cuture filtrate Cryptococcus neoformans’s var. gattii. The results of coagulation tests (PT, PTT, CT and BT) and the renal histopathological changes compared with control group. Insignificant difference between related tests in control and test groups were observed, therefore results of this research proposed capsular compounds have no effect on blood coagulative process and renal performance in persons who involved in cryptococcosis.